Primary cutaneous adenoid cystic carcinoma of the scalp: A case report, immunohistochemistry and review of the literature - Bhakinai Temnithikul; Suthat Rungrunanghiranya; Piyakan Limtanyakul; Suthep Jerasuthat; David G. Paige (Wiley, 2022)
Abstract Primary cutaneous adenoid cystic carcinoma (PCACC) is an uncommon adnexal skin tumour with fewer than 200 cases studied in detail in the English literature. We describe the diagnosis and treatment of a few Southeast Asian cases of PCACC on the scalp of a 70‐year‐old Thai female. She presented with a slow‐growing, painless, solid to cystic, skin‐coloured tumour on her scalp. When excisional biopsy was done, histopathological findings showed dermal tumour that had a classic histologic appearance composed of basaloid cells arranged in a cribriform pattern with 'punched‐out' pseudocysts filled with mucin (swiss cheese pattern) and had perineural invasion. The clinical and histopathological findings, and complete investigations confirmed the diagnosis of PCACC. Our case illustrates that PCACC, is an important histopathological differential diagnosis to bear in mind due to its locally aggressive nature and tendency to recur due to perineural invasion. A wide local excision with at least 2 cm of tumour‐free margins was performed, which revealed no residual carcinoma. The patient remained disease‐free for 16 months after diagnosis. PCACC is usually located on the head or neck of people in their sixth decade of life, with a female predominance. The aetiology of PCACC is unclear. The majority of PCACCs have the MYB‐NFIB fusion gene or show overexpression of MYB by immunohistochemistry. Diagnosis of PCACC is primarily based on the characteristic histological appearance, as there are no distinguishing clinical features. The diagnosis of PCACC requires careful exclusion of infiltration or metastasis from other primary lesions. Treatment of this rare tumour is wide surgical excision with at least 2 cm of tumour‐free margins to reduce the risk of local recurrence, and long‐term follow‐up for possible recurrence of PCACC is recommended. This case emphasizes the importance of careful inspection for the diagnosis of PCACC after initial surgery and pathological evaluation of the mass lesion for appropriate diagnosis and therapy.